The maple festival - Green, Poppy; Bell, Jennifer (Jennifer A.), 1977- (New York : Little Simon, 2015)
"Sophie helps her mother bake maple treats for the annual Maple Festival in Silverlake Forest. When she notices no one at her mother's stand, she must find a way to attract more visitors"--
Keywords: Baking -- Juvenile fiction; Autumn -- Juvenile fiction; Festivals -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Juvenile fiction